2008
DOI: 10.2478/s11772-008-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy extended with indocyanine green dye dilution for cerebral blood flow measurement: Median values in healthy volunteers

Abstract: The cerebral blood flow (CBF) is an important vital parameter in neurointensive care. Currently, there is no non-invasive method for its measurement that can easily be applied at the bedside. A new tool to determine CBF is based on near-infrared spectroscopy (NIRS) applied together with indocyanine green (ICG) dye dilution. From a bilateral measurement on selected regions on the head of infrared (IR) absorption at various wavelengths during the dilution maneuver, the vascular perfusion characteristics of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…It has been previously reported that the ICG bolus-tracking method combined with CW-NIRS underestimates CBF in adults by a factor of 3 due primarily to the overestimation of the optical path length through brain tissue. 13,14 Improved depth sensitivity has been achieved using photon time-of-flight information measured directly by time-resolved ͑TR͒ techniques, or indirectly through phase changes measured by frequency-domain ͑FD͒ techniques. [15][16][17][18] The depth sensitivity made available by these techniques is due to the fact that early arriving photons travel shorter distances ͑i.e., through superficial tissue͒, while late arriving photons travel longer distances ͑i.e., deeper into brain tissue͒.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that the ICG bolus-tracking method combined with CW-NIRS underestimates CBF in adults by a factor of 3 due primarily to the overestimation of the optical path length through brain tissue. 13,14 Improved depth sensitivity has been achieved using photon time-of-flight information measured directly by time-resolved ͑TR͒ techniques, or indirectly through phase changes measured by frequency-domain ͑FD͒ techniques. [15][16][17][18] The depth sensitivity made available by these techniques is due to the fact that early arriving photons travel shorter distances ͑i.e., through superficial tissue͒, while late arriving photons travel longer distances ͑i.e., deeper into brain tissue͒.…”
Section: Introductionmentioning
confidence: 99%
“…This method was used on an optical signal collected with probes on the scalp and inside the skull. 3032…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
“…Based on the modified Beer–Lambert law, the ICG concentration in the tissue citalicICGitalictissue was linked to the change in OD before and after the ICG injection 30 where italicDPF is the differential pathlength factor and d is the distance between the source and the detector.…”
Section: Cerebral Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Own examinations in 10 healthy volunteers allowed the definition of normal values with the new measurement setting [122]. ICG (0.5mg per kg bodyweight) was injected into the antecubital vein.…”
Section: Normal Values Critical Thresholdsmentioning
confidence: 99%